Broadband Ge/SiGe quantum dot photodetector on pseudosubstrate - Yakimov, Andrew (Springer, 2013)
We report the fabrication and characterization of a ten-period Ge quantum dot photodetector grown on SiGe pseudosubstrate. The detector exhibits tunable photoresponse in both 3- to 5- μm and 8- to 12- μm spectral regions with responsivity values up to about 1 mA/W at a bias of −3 V and operates under normal incidence radiation with background limited performance at 100 K. The relative response in the mid- and long-wave atmospheric windows could be controlled through the applied voltage.